Designing and Developing Self-Directed Learning Resources in Open Distance Learning (ODL) Contexts: A Ghanaian Case Study (Teacher Education through Flexible Learning in Africa (TETFLE), 2025)
The expansion of Open and Distance Learning (ODL) is critical for teacher education in Ghana. This study explores the on-the-ground reality of how educational resources are designed, developed, and used within a major Ghanaian university’s ODL teacher education programme. Using qualitative case study design, semi-structured interviews were conducted with 15 participants, comprising curriculum developers, module authors/lecturers, and course tutors. Findings reveal a systematic approach centred on collaborative co-authoring to create interactive, self-directed print textbooks locally referred to as modules, which serve as primary learning materials. The design approach emphasises interactive self-study, enabling learners to engage with content independently. However, significant challenges emerge from a systemic fragmentation between content creation and delivery. Tutors, who are at the forefront of implementation, have limited formal channels for providing feedback, leading to a disconnect between the intended and enacted curriculum. The current study highlights the need for greater pedagogical coherence and institutionalised feedback loops to enhance the quality and effectiveness of ODL resources in this context.
Keywords: Curriculum development; Ghana; Open and Distance Learning (ODL; resource design; teacher education